PERSEPSI PESERTA DIDIK TERHADAP GAMIFIKASI DALAM PEMBELAJARAN: STUDI KASUS DI SMA SANTO PAULUS PONTIANAK - Suliono Suliono; Indri Astuti; Afandi (PendIPA Journal of Science Education, 2023)
This study aims to determine the students' perceptions of SMA Santo Paulus Pontianak regarding the application of gamification in chemistry learning. The research is a case study with a survey method conducted at SMA Santo Paulus Pontianak. The study was conducted on 302 students in class X. Students' perceptions of gamification were surveyed using the Q-method Analysis instrument. A guided free interview technic used to confirm the questionnaire results and obtain additional information or clarify gaps in the questionnaire results. The results of this research as a whole get an average survey result (approval of positive statements and disagreement of negative) of 78.2%, which indicates that students have positive perceptions with good categories on the application of gamification in chemistry learning. The conclusion from the results of this study is that the application of gamification makes teaching and learning activities fun. Aspects of gamification provide a variety of learning activities. Students are motivated to achieve the best possible learning outcomes because of the competitive and collaborative nature fostered by numerous positive feedbacks and reinforcements.